Dynamics of the epidemic process and the course of the COVID-19 in pregnant women of the Far Eastern and Siberian Federal Districts - Tatiana E. Belokrinitskaya; Natalya V. Artymuk; Oleg S. Filippov; Efim M. Shifman (IP Berlin A.V., 2020)
The objective of the study was to evaluate an epidemiological characteristic and the course of COVID-19 in pregnant women from the Far East and Siberian Federal Districts of Russia. Materials and methods. The analysis of operational information on the incidence of COVID-19 and the its features in pregnant women and after childbirth provided by the chief obstetrician-gynecologists of the Far Eastern Federal District and Siberian Federal District on May 25, 2020 and August 25, 2020 is carried out. Mathematical analysis included descriptive statistics methods, analysis of contingency tables, where the 2 value, the achieved significance level (p) Results. On August 25, 2020, 2010 cases of COVID-19 in pregnant women were detected in two subjects, including 134 active cases. In the population, the proportion of pregnant women among cases of COVID-19 was 1.45%. Pneumonia in pregnant women was registered in 44.8% of cases, severe course of the disease - in 3.7%, hospitalization in RAW - in 1.9% of cases, mechanical ventilation - 0. In the population, pneumonia was registered in 24.4% of cases, hospitalized in RAW - 2.1%, on mechanical ventilation - 0.77%. The incidence in pregnant women was 1464.7 per 100000 (in the population - 591.8 per 100 000). 23 (1.76%) COVID-19 (+) newborns were identified, despite preventive measures and separation of mother and child immediately after childbirth, which does not exclude vertical transmission of the disease. Maternal mortality was 2 cases (0.1%) vs population mortality 1.49%. Perinatal mortality was 7 cases (0.35%). There were 5 (0.25%) stillbirths. Early neonatal mortality was 2 (0.1%) cases. Conclusion. The incidence of COVID-19 in pregnant women in the Far East and Siberia is higher than in the general population with a higher incidence of pneumonia, but a milder course: less need for ICU, mechanical ventilation and mortality. 23 cases of SARSCoV-2-positive newborns, despite the separation of mother and child, do not exclude the possibility of vertical transmission of infection. Keywords: COVID-19, pregnancy, epidemiology, incidence, pneumonia, mortality